2022
DOI: 10.1111/josi.12516
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in young people's evaluations of sexual harassment

Abstract: Using an accelerated longitudinal design, we investigated developmental changes in young peoples’ evaluations of sexual harassment (SH) and how young peoples’ own experiences with harassment, their perceptions of teacher intervention, as well as how gender and sexual orientation related to their judgments. This study documented significant changes in adolescents’ evaluations of peer‐based SH from grades 7 to 10. Overall, there was a significant decrease in the extent to which youth judged SH to be wrong as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Importantly, peer norms were often stereotypically gendered, putting pressure on young men/boys to engage in sexual harassment to appear masculine, and putting shame and blame on girls for being sexually harassed (Ringrose & Regehr, 2023). This is in line with the findings showing that girls/women were less tolerant of sexual harassment (Herry & Mulvey, 2022; Horn & Poteat, 2022) and suffered more severe psychological consequences of sexual harassment than boys/men (Skoog & Kapetanovic, 2022). In addition, at the microlevel, the actions of teachers and the school climate regarding sexual harassment also shape the norms related to sexual harassment among young people.…”
Section: Cross‐cutting Themessupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, peer norms were often stereotypically gendered, putting pressure on young men/boys to engage in sexual harassment to appear masculine, and putting shame and blame on girls for being sexually harassed (Ringrose & Regehr, 2023). This is in line with the findings showing that girls/women were less tolerant of sexual harassment (Herry & Mulvey, 2022; Horn & Poteat, 2022) and suffered more severe psychological consequences of sexual harassment than boys/men (Skoog & Kapetanovic, 2022). In addition, at the microlevel, the actions of teachers and the school climate regarding sexual harassment also shape the norms related to sexual harassment among young people.…”
Section: Cross‐cutting Themessupporting
confidence: 90%
“…Beginning with the individual level, several studies showed that young people's own attitudes toward sexual harassment were related to the occurrence of sexual harassment and how the young people experienced it. Findings from Horn and Poteat's longitudinal study (2022) showed that young people became more tolerant of peer sexual harassment as they grew older, and the authors noted that this developmental change is in line with the peak of sexual harassment in adolescence (see also Li et al., 2022). More tolerant attitudes were also held during times when sexual harassment was more frequent, indicating that these actions were then more justified in young people's attitudes.…”
Section: Cross‐cutting Themesmentioning
confidence: 98%
“…With the current design, we were only able to examine the roles of ethnicity and gender in the associations. Young people's attributional styles and coping abilities are two other potential third variables, as they both have been found to be important for the impact of sexual harassment among youth (see e.g., Horn & Poteat, 2023). Also, our measure of ethnicity (studying Swedish as a second language) can only be considered to be a proxy for ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…This will undoubtedly negatively impact if the existing peer environment provides negative support. This is also a step to strengthen the school's alignment as a formal institution towards student problems (Horn & Poteat, 2022). It was also found that the role of online media can stimulate younger children to try deviant sexual behavior, so that healthy use of the internet needs to be a concern at a young age because internet access is now much more accessible (Raine et al, 2020).…”
Section: }mentioning
confidence: 99%